Impact of a gene expression classifier on the long-term management of patients with cytologically indeterminate thyroid nodules. (2nd July 2016) - Singer, Joseph; Hanna, John W.; Visaria, Jay; Gu, Tao; McCoy, Mark; Kloos, Richard T.
Abstract: Objectives : The gene expression classifier (GEC, Afirma * ) reclassifies as molecularly benign approximately one half of thyroid nodule fine-needle aspiration (FNA) biopsies with an initial indeterminate cytopathology diagnosis, facilitating clinical monitoring in lieu of diagnostic thyroid surgery. This study evaluated the long-term management patterns and thyroid surgery rates of GEC benign patients compared to a control group of cytopathology benign patients and also described the costs of thyroid surgery.Methods : This retrospective cohort study used laboratory test results linked to payer medical claims data. Patients who underwent FNA biopsy between 1 January 2011 and 31 July 2013 were selected. GEC benign patients were matched 1:3 to cytopathology benign patients on biopsy year, gender, nodule size and age. Outcomes measured included thyroid-related follow-up clinic visits, ultrasound examinations and surgeries.Results : Out of 2059 patients, matched groups consisting of 201 GEC benign patients and 603 cytopathology benign patients were evaluated over an average follow-up of 20 months. The proportions of GEC benign and cytopathology benign patients that underwent thyroid surgery (11.4% versus 10.1%, p  = 0.594), and received a follow-up ultrasound exam (60.2% versus 61.7%, p  = 0.706), respectively, were not significantly different. Average thyroid-related medical cost for the surgical episode and during 6 months following surgery were $10, 432.00 (SD $8301) and $10, 939.00 (SD $9656) respectively.Limitations : The study cohort included only patients whose diagnostic laboratory test results and administrative claims data were uniquely identifiable and could be linked on multiple identifiers; the rigorous matching and patient selection algorithms utilized improved the robustness and internal validity of the study. Claims were used as a proxy for clinical utilization without chart review confirmation.Conclusion : Patients with GEC and cytopathology benign diagnoses were managed similarly. The majority of patients in both groups did not undergo surgery and were managed with usual care, consisting of clinical follow-up and ultrasound exams.